KOMIK âHUJAN BULAN JUNIâ KARYA MANSYUR DAMAN: ANALISIS SEMIOTIKA ROLAND BARTHES - , M DANIEL FAHMI RIZAL; , Dr. Aprinus Salam ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Comic is a form of art that combine the elements of visual and text. Comic also has the potential to become a literary work. One of many comic that included as a literary work is \"Hujan Bulan Juni\" by Mansyur Daman or commonly known as Man. \"Hujan Bulan Juni\" is a comic strip that was published in the 6th edition of Comical Magz bulletin in 2011. It was the transformation of a poem by Sapardi Djoko Damono with the same title. This researh is purposed to explain the meaning contained in \"Hujan Bulan Juni\" comic. The theory that will be used is Roland Barhes's semiotics. Roland Barhes's semiotic theory explain an analysis through the text separation into leksias in order to find codes which possibly create a meaning. Morover, another text outside the comic will be used as supportive information or statement to deeply reveal the meanings implied in this comic. The result of this research is to show that \"Hujan Bulan Juni\" comic is the feeling of love that comes not at the right time. The feelings experienced by one of the characters in the story. Despite the love which does not come on time , the main character of the comic starts to show good deed as the impact of his experience. The naration and attitude shown by the main character through captions and actions on te pictures contained in the panels of the comic.